Thionation of asymmetric rylene diimides - Pearce, Nicholas (2016)
Rylene diimides have attracted much attention for use in optoelectronic devices, with excellent absorption and emission profiles, as well as a tendency to form n-type semiconductors. The absorption and emission properties of rylene diimides can be varied through functionalisation at the imide nitrogens and by substitution to the aromatic core but the effects of alterations to the imide oxygen atoms are less well understood. A series of thionated naphthalene diimides (NDIs), in which the imide oxygen atoms have been replaced with sulfur has been synthesised in a single reaction using Lawesson’s reagent. Electrochemical measurements of the series reveal that the electron affinity increases significantly with sulfur substitution, making the singly and doubly reduced states of the NDI much more accessible. This work is expanded further with the production of asymmetric NDI and naphthalic imide systems. Phenothiazine is employed as an electron donor and thionated derivatives of NDIs and naphthalic imides are implemented as the electron acceptors. Photoinduced charge separation was observed for these dyads using a combination of picosecond time-resolved transient absorbance spectroscopy and infrared spectroscopy, finding that thionation increases the charge separated lifetime of the species by a factor of ten; producing radical pairs with lifetimes greater than 2 ns, sufficient for charge extraction in organic electronic devices. Perylene diimides (PDIs) are related to NDIs, but with a larger aromatic core. Despite an enhancement of desirable properties relative to NDIs, the practicality of PDIs can be limited by low solubility and demanding syntheses. As the field of supramolecular chemistry expands, the synthesis of more sophisticated molecular arrays has become necessary to build improved nanotechnological components. Herein, the effectiveness of a bulky aromatic solubilising group for PDIs is examined crystallographically and used to synthesise a range of soluble N,N’-asymmetrically disubstituted PDI compounds. The applications of this new solubilising group were demonstrated in the production of a multichromophoric PDI dimer; in the assessment of binding affinity of a hydrogen-bonding PDI to the nucleobase adenine and finally in the synthesis of a charge transfer complex, again utilising phenothiazine as an electron donor. This charge transfer complex was also thionated, providing a unique perylene monoimide monothiomide with an experimentally determined band gap of approximately 1 eV.